Evaluation of lumican effects on morphology of invading breast cancer cells, expression of integrins and downstream signaling. (31st March 2020) - Karamanou, Konstantina; Franchi, Marco; Onisto, Maurizio; Passi, Alberto; Vynios, Demitrios H.; Brézillon, Stéphane
Abstract : The small leucine‐rich proteoglycan lumican regulates estrogen receptors (ERs)‐associated functional properties of breast cancer cells, expression of matrix macromolecules, and epithelial‐to‐mesenchymal transition. However, it is not known whether the ER‐dependent lumican effects on breast cancer cells are related to the expression of integrins and their intracellular signaling pathways. Here, we analyzed the effects of lumican in three breast cancer cell lines: the highly metastatic ERβ‐positive MDA‐MB‐231, cells with the respective ERβ‐suppressed (shERβMDA‐MB‐231), and lowly invasive ERα‐positive MCF‐7/c breast cancer cells. Scanning electron microscopy, confocal microscopy, real‐time PCR, western blot, and cell adhesion assays were performed. Lumican effects on breast cancer cell morphology were also investigated in 3‐dimensional collagen cultures. Lumican treatment induced cell–cell contacts and cell grouping and inhibited microvesicles and microvilli formation. The expression of the cell surface adhesion receptor CD44, its isoform and variants, hyaluronan (HA), and HA synthases was also investigated. Lumican inhibited the expression of CD44 and HA synthases, and its effect on cell adhesion revealed a major role of α1, α2, α3, αVβ3, and αVβ5 integrins in MDA‐MB‐231 cells, but not in MCF‐7/c cells. Lumican upregulated the expression of α2 and β1 integrin subunits both in MDA‐MB‐231 and in shERβMDA‐MB‐231 as compared to MCF‐7/c cells. Downstream signaling pathways for integrins, such as FAK, ERK 1/2 MAPK 42/44, and Akt, were found to be downregulated by lumican. Our data shed light to the molecular mechanisms responsible for the anticancer activity of lumican in invasive breast cancer. Abstract : Lumican regulates ERs‐associated functional properties of breast cancer cells, expression of matrix macromolecules, and EMT. Lumican treatment of cells favors cell–cell contacts and cell grouping and results in smoother cell surface with fewer microvesicles and microvilii, the downregulation of HA synthases and CD44, and has a variable effect on 2 and 1 integrin subunit expression. Integrin and downstream signaling pathways (FAK, ERK1/2, MAPK42/44, and Akt) are downregulated by lumican.